Top 100 most-cited articles on hemorrhoids: A bibliometric analysis and visualized study - Wang, Zhaochu; Wu, Xuxiong; Li, Yang; Huang, Juan; Shi, Rong; Wang, Jing (Frontiers in Surgery, 2022)
Background: Hemorrhoids have a significant incidence in people and are becoming a common public health problem. This study provides a bibliometric and visualized analysis of the most influential literature in the field. The aim is to reveal trends in the field of hemorrhoids and to provide a reference for researchers. Methods: The 100 most frequently cited studies in the field of hemorrhoids were collected from the Web of Science(WOS), and were analyzed in terms of the annual publication, types of literature, countries, institutions, authors, journals, and keywords. During the study, we used a combination of VosViewer, Carrot2, Microsoft Excel, and Tableau tools to better present the visual information. Results: A total of 4,481 papers were searched and the 100 most frequently cited papers had a frequency ranging from 92–1090. Few essential studies were published before 1990, and since then, there has been an irregular growth trend. All countries of the publications are coastal, with the U.S. and the UK contributing many more than the others. Imperial College London has published the most influential articles in the field of hemorrhoid disease. Kamm MA and Phillips RKS are the most authoritative authors in the field. Diseases of the Colon & Rectum and the British Journal of Surgery are the most influential journals in this field. The most famous focus in the field of hemorrhoid research is the evolution of stapled hemorrhoidectomy (SH) and Milligan-morgan hemorrhoidectomy (MMH). Conclusions: This study is the first to explore developments in the field of hemorrhoids. It helps surgeons quickly understand global trends in the field of hemorrhoids, mainly through the latest surgical developments, which may be one of the most accessible directions for generating research results. The results of this study are intended to add to the attention and interest of scholars in this area and provide a reference for further research.